Quantitative analysis of the dominant external factors influencing elite speed Skaters' performance using BP neural network - Yang, Zhenlong; Ke, Peng; Zhang, Yiming; Du, Feng; Hong, Ping (Frontiers in Sports and Active Living, 2024)
Speed skating, being a popular winter sport, imposes significant demands on elite skaters, necessitating their effective assessment and adaptation to diverse environmental factors to achieve optimal race performance. The aim of this study was to conduct a thorough analysis of the predominant external factors influencing the performance of elite speed skaters. A total of 403 races, encompassing various race distances and spanning from the 2013 to the 2022 seasons, were examined for eight high-caliber speed skaters from the Chinese national team. We developed a comprehensive analytical framework utilizing an advanced back-propagation (BP) neural neural network model to assess three key factors on race performance: ice rink altitude, ice surface temperature, and race frequency. Our research indicated that the performance of all skaters improves with higher rink altitudes, particularly in races of 1000 meters and beyond. The ice surface temperature can either enhance or impaire performance and varies in its influences based on skaters' technical characteristics, which had a perceptible or even important influence on races of 1500 meters and beyond, and a negligible influence in the 500m and 1000m races. An increase in race frequency generally contributed to better performance. The influence was relatively minor in the 500m race, important in the 3000m race, and varied among individuals in the 1000m and 1500m races. The study results offer crucial guidelines for speed skaters and coaches, aiding in the optimization of their training and competition strategies, ultimately leading to improved competitive performance levels.